Populasi Bakteri Dan Jamur Serta Pertumbuhan Tanaman Teh (Camellia sinensis L.) Pada Dua Jenis Media Tanam Setelah Inokulasi Azotobacter - Reginawanti Hindersah; Bagus Adityo; Pujawati Suryatmana (Faculty of Agriculture, Pattimura University, 2016)
Substituting a part of soil on tea Camellia Sinensis (L.) O. Kuntze) nurseries by using organic matter could minimize the remove fertile soil from nature. Biofertilizing are a way to improve the biological quality of soil and subsequently tea seedling quality. The aim of the research was to determine the effect of planting media composition and biofertilizer doses on total fungal and bacterial population on planting media; as well as tea seedlings growth. The experiment was conducted using a randomized block design consisting of 9 treatments and 4 replications, each replication consisted of three plants. The treatment consisted of soil without biofertilizer (control), soil + 5% biofertilizer, soil + 10% biofertilizer, cocopeat without biofertilizer, cocopeat + 5% biofertilizer, cocopeat + 10% biofertilizer, filter cake without biofertilizer, filter cake + 5% biofertilizer, and filter cake + 10% biofertilizer. Biofertilizer used in this experiment were Azotobacter vinelandii and Azotobacter chroococcum that was mixed with growing media before planting. Result of the experiment showed that planting media affect microbial populations differently. The population of total bacteria, total fungi and Azotobacter sp. in the filter cake media with 10% biofertilizer was significantly higher than those of other growing media. However, Azotobacter biofertilizer had no effect on seedling growth of tea (Camellia Sinensis (L.) O. Kuntze) clones Gambung-7